2021
DOI: 10.12659/msm.932962
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Neurological Involvement in Patients with SARS-CoV-2 Infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative pathogen of the recent pandemic of coronavirus disease 19 (COVID-19). As the infection spreads, there is increasing evidence of neurological and psychiatric involvement in COVID-19. Headache, impaired consciousness, and olfactory and gustatory dysfunctions are common neurological manifestations described in the literature. Studies demonstrating more specific and more severe neurological involvement such as cerebrovascular insults, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 92 publications
0
12
0
5
Order By: Relevance
“…In addition, Cocco et al 38 found a significant relationship between OD and altered trigeminal sensation. Moreover, Xu et al 39 have suggested trigeminal nerve as putative neuroanatomical route for SARS‐CoV‐2 dissemination. More precise studies on this subject are needed but these data could be interesting to understand the pathway of SARS‐CoV‐2 to the nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Cocco et al 38 found a significant relationship between OD and altered trigeminal sensation. Moreover, Xu et al 39 have suggested trigeminal nerve as putative neuroanatomical route for SARS‐CoV‐2 dissemination. More precise studies on this subject are needed but these data could be interesting to understand the pathway of SARS‐CoV‐2 to the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“… 27 on post‐mortem samples demonstrated the presence of RNA and viral protein of SARS‐CoV‐2 in the brain. Two paths to the central nervous system have been proposed, 39 the first by axonal transport through the olfactory bulb after infection of basal cells expressing ACE2. The second one by hematogenous transport by destruction of the endothelial cells of the blood‐brain barrier or via immune cells expressing ACE2 (dendritic cells, macrophages) in the manner of a Trojan horse.…”
Section: Discussionmentioning
confidence: 99%
“…Among those, neurological manifestations, ranging from olfactory dysfunction to any neurologic manifestation, with the most common being encephalopathy, have been of great concern since the beginning of the pandemic [ 11 , 38 ]. The mechanisms accounting for the onset of neurological symptoms/complications in certain COVID-19 patients is still matter of study, especially in terms of the role directly played by the virus [ 11 , 28 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort of patients, four were between 25 and 35 years old, one around 55 and two above 70 years old. Neurological symptoms and complications displayed by the selected subjects are reported in the literature among the most frequent COVID19-related neurological manifestations [ 13 , 39 ]. All patients in the most severe neurological conditions presented important respiratory symptoms, such as interstitial pneumonia, and were intubated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of severe neurological disorders such as encephalitis have been also observed in patients with COVID-19 disease 13 , 14 , 15 , 16 . In this regard, clinical studies have shown that some patients infected with COVID-19 have symptoms similar to those of intracranial infections such as headache, epilepsy, and impaired consciousness 17 , 18 , 19 , 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%